A hue and warm‐cool model for warm‐cool based correlated color temperature calculation. Issue 4 (6th December 2021) - Oh, Semin; Kwak, Youngshin
Abstract: Correlated color temperature is widely used to describe colors of lights, but it has been questionable if it is well correlated to real perception. This study approached this issue with warm‐cool feelings, that is, the same correlated color temperature would evoke the same level of warm‐cool feelings. Since warm‐cool feeling is widely accepted to correlate closely with hue, a psychophysical experiment was performed to collect visual data of lights in terms of both hue and warm‐cool feelings. As a result, the hue and the warm‐cool prediction models were, respectively, proposed. The proposed hue model has the same structure with CAM16 with new degree of adaptation considering the luminance and chromaticity and unique hue angle settings for lights. The warm‐cool model can be used in conjunction with the hue model, which enables to assign the correlated color temperature based on the warm‐cool feelings as a new calculation method for correlated color temperature that is expected to achieve a better visual resemblance. Abstract : An example to compare the calculation results of correlated color temperature (CCT) and warm‐cool based correlated color temperature (CCT‐WC)